W boson mass and Properties - Hays, C (2005)
Measurements of the W boson determine fundamental parameters of the standard model and test its internal consistency at the level of radiative corrections. In particular, the W boson mass constrains the mass of the unobserved Higgs boson through loop corrections, and the W boson width indirectly determines elements of the CKM matrix defining quark generational mixing in the electroweak interactions. The CDF Collaboration has analyzed ≈200 pb -1 of s=1.96TeV pp̄ collision data and determined the uncertainty on its W boson mass measurement to be 76 MeV. The DØ Collaboration has directly measured the W boson width to be Γ W = 2.011 ± 0.09(stat.)±0.107(syst.) GeV using 177 pb -1 of W → ev data. © 2005 American Institute of Physics.